Potassium extractability from soils of brazilian coffee regions (Bioscience Journal, 2012)
Coffee, which is an important commodity for Brazil, is a highly K-demanding crop. Methods for recommending K fertilization to coffee crops in Brazil are based on the amount of exchangeable K. Mineralogical studies estimating K supply capacity from different soil fractions, from medium to long term, were performed in Brazilian soils, but very few studies have been carried out focusing on the use of successive chemical extractions. This study evaluated K release from whole soil, as well as clay, silt, and sand fractions of B-horizon samples of a basalt-derived Oxisol and a sienite-derived Ultisol, both representative soils from coffee regions of Minas Gerais State. Successive extractions (0 to 665 h) of K were performed with 10-3 mol L-1 of either citrate or oxalate at 1:10 solid:solution ratio. The cumulative results were compared with forms of K (exchangeable, non-exchangeable, and total) as measured by different extraction procedures. The results showed that exchangeable K was higher, and non-exchangeable as well as total K were lower in the whole soil fraction of the Oxisol, than the K forms extracted from the Ultisol. The clay fraction was the main source of K in the Oxisol whereas the silt fraction contributed most for K supply in the Ultisol. Citrate and oxalate extracted similar amounts of K from the Oxisol, which is probably related to the fact that most of its K supply came from the exchangeable form. Citrate caused a greater release of K (part of which being from the non-exchangeable form) from the Ultisol than did oxalate. This work showed that soil texture alone is not a good indicator of K supply capacity, since for the same particle size, the studied soils revealed different K extractability.